2015
DOI: 10.1108/jocm-11-2013-0225
|View full text |Cite
|
Sign up to set email alerts
|

Public sector work intensification and negative behaviors

Abstract: Purpose -The purpose of this paper is to explore issues associated with sector specific change in the Australian Public Service (APS). Evidence is presented on the impact of New Public Management (NPM) on work intensification and subsequent negative behaviors by giving voice to APS employees who were subject to the NPM changes.Design/methodology/approach -Data were collected from APS employees, human resource managers and policy makers across 11 agencies on the nature of the changes, context of work, and workp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 24 publications
2
28
0
1
Order By: Relevance
“…The findings of this study indicate that employees from Chinese-owned companies are of the view that due to lack of job security, employees tend to tolerate a lot from the employers, for fear of being dismissed from work, and this is supported by other studies in a similar context (Fajana, 2008;Giese & Thiel, 2015;Iyanda, 1999;Omari & Paull, 2015). In the present study, it is evident that there is a positive relationship between employment status and job insecurity and this is consistent with Wang et al (2016).…”
Section: Journal Of Management Researchsupporting
confidence: 84%
“…The findings of this study indicate that employees from Chinese-owned companies are of the view that due to lack of job security, employees tend to tolerate a lot from the employers, for fear of being dismissed from work, and this is supported by other studies in a similar context (Fajana, 2008;Giese & Thiel, 2015;Iyanda, 1999;Omari & Paull, 2015). In the present study, it is evident that there is a positive relationship between employment status and job insecurity and this is consistent with Wang et al (2016).…”
Section: Journal Of Management Researchsupporting
confidence: 84%
“…However, little is known about how respect is associated with negative workplace behaviours in a collectivist culture. Most of the researches on respect are being examined in the Western society (see Omari and Paull 2015) that found that a lack of respect tends to be the cause of negative workplace experience in the public sector. Given the importance of a respectful workplace culture (Omari and Paull 2015), the second contribution in our study is to examine how respect diminishes the occurrences of negative workplace behaviours in order to enhance positive employee work outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the researches on respect are being examined in the Western society (see Omari and Paull 2015) that found that a lack of respect tends to be the cause of negative workplace experience in the public sector. Given the importance of a respectful workplace culture (Omari and Paull 2015), the second contribution in our study is to examine how respect diminishes the occurrences of negative workplace behaviours in order to enhance positive employee work outcomes. Negative workplace behaviours are associated with leaders not listening to the voices of their subordinates, or not recognizing the employees' needs (Cowell, Downe, and Morgan 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the impact of NPM reforms have long highlighted the importance of devoting special attention to human resources policies, both to mitigate their unintended effects of reforms and to support the reform processes themselves (Michie and West, 2004). Recent studies dedicated to the processes of change in the public sector (Kellis & Ran, 2015), have observed how the NPM reforms are destined to remain incomplete if not able to actively involve workers in them by responding to their needs (Omari and Paull, 2015), their ethical standards and their public service motivation (Vandenabeele et al, 2006).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…For people already employed in the public sector, the NPM reforms have led to a substantial change in their organizational roles determining an increasingly competitive (internal and external) relationship context (Hood 1995). This led to consequences with regards to work intensification (Omari and Paull, 2015) leading to increases in job-related stress (Noblet, Rodwell, and McWilliams;. Furthermore perceived job insecurity (Pink 2011) rose, followed by a reduction of the individual engagement (Brunetto, 2014), intrinsic motivation (Perry and Hondeghem 2008) and job satisfaction in the workplace (Brunetto, 2005).…”
Section: Introductionmentioning
confidence: 99%